STRATEGI KEUANGAN UMKM CILACAP MENGHADAPI PANDEMI COVID 19 (STUDI KASUS UMKM KABUPATEN CILACAP) - Kuswantoro, Kuswantoro; Alfi, Imam (Jurnal Teknologi dan Bisnis, 2020)
In Indonesia, the corona virus has spread to various regions, one of which is in the Cilacap Region. This has an impact on many sectors, one of which is the disrupted economic sector. Many large companies and factories have closed down and laid off employees. What is the UMKM financial strategy in Cilacap in dealing with the economic slowdown due to the corona virus. This research is a qualitative research through field studies using observation and interviews with UMKM actors. Based on the research results of the First Application of Government Policy in the context of Co-19 Handling, UMKM experienced a decrease in income. Second. Strategic steps are needed to overcome the financial problems of UMKM that are decided based on good and appropriate research. One appropriate method is to use the boom, downturn, bottom, and upword approaches. With this model it is hoped to be the solution to that problem.